2017
DOI: 10.2147/ppa.s149412
|View full text |Cite
|
Sign up to set email alerts
|

A new pen device for injection of recombinant human growth hormone: a convenience, functionality and usability evaluation study

Abstract: PurposeAdherence to recombinant human growth hormone (r-hGH) is critical to growth and other outcomes in patients with growth disorders, but the requirement for daily injections means that ease of use is an important factor. This study assessed the perceived ease of use and functionality of the prototype of a reusable pen injector (pen device) for r-hGH that incorporates several advanced features.Participants and methodsSemi-structured 60-minute qualitative interviews were conducted in 5 countries with 57 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The new pen device incorporates several features that are designed to improve the user experience, such as an aluminum body, a multi-use cartridge system, cartridge viewing and dose display windows, a rotating dose selection knob, and an injection button. This evaluation showed that the pen device and associated materials could be used safely and effectively by the intended users, similar to the outcome reported after the functionality and ease of use testing of the pen device [10]. The testing process presented here is consistent with other usability engineering assessments for pen devices [17][18][19][20].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The new pen device incorporates several features that are designed to improve the user experience, such as an aluminum body, a multi-use cartridge system, cartridge viewing and dose display windows, a rotating dose selection knob, and an injection button. This evaluation showed that the pen device and associated materials could be used safely and effectively by the intended users, similar to the outcome reported after the functionality and ease of use testing of the pen device [10]. The testing process presented here is consistent with other usability engineering assessments for pen devices [17][18][19][20].…”
Section: Discussionsupporting
confidence: 81%
“…The Aluetta™ pen device is a reusable, multi-dose injection pen for use with r-hGH (Somatropin [Saizen®], Merck KGaA, Darmstadt, Germany) [10]. The new pen device was designed to provide an easy to use, lightweight, reusable, multi-dose injection device for patients injecting Saizen®.…”
Section: Introductionmentioning
confidence: 99%
“… 21 The widespread acceptance of pre-filled injection devices is, therefore, driven by a range of benefits including convenience, simplicity, suitability for home use, reduction in wasted products and associated environmental benefits, and greater dose precision. 12 , 13 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…In the current study, a list of attributes of a pre-filled gonadotropin self-injection pen device was prepared which contained a total of 14 options ( Table 1 ). The options were selected to reflect standard attributes investigated in prior research and similar publications examining pre-filled injection pens 13 , 20 , 21 and were validated by feedback obtained from fertility specialist nurses regarding features of pen devices that were considered to be of greatest importance. Attributes were intended to cover key areas including training, injection preparation, injection experience, how the injection fits into the patient’s daily routine and the overall appearance/look of the injection pen.…”
Section: Methodsmentioning
confidence: 99%
“…5 Prefilled syringes ensure accurate dosing, sterility, and improved safety. 6 Consequently, the development of self-injection devices has improved patient acceptance of injections, ease of use compared with the conventional needle and syringe, 7 and patient experience and preference. 8 Newer autoinjector technologies are designed to further ease patient burden, facilitate self-injection, and improve treatment adherence and convenience; 6,8 these are considered by healthcare professionals to be advantageous to manual syringe injections.…”
Section: Introductionmentioning
confidence: 99%